PERANCANGAN PROGRAM SIMULASI PERINTAH DASAR JARINGAN KOMPUTER - Joefrie, Yuri Yudhaswan (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2013)
This research is intended to design software that is able to simulate the basic commands of the computer network. Simulation program is planned to serve for people who do not understand about computer networks and have a strong desire learning the basics of computer networks. The design result of this research is commandÂ  of ping, telnet, ftp, route, and ifconfig. The design of the simulation program also produces 10 units or classes that contain the components of the specific activity or program. Keyword: simulation program, computer network, basic command of computer network.